KIAI LEADERSHIP IN COACHING IS ENTREPRENEURSHIP SKILLS PESANTREN SCHOOL STUDENTS - Muhammad Mukhlis Izzat; Sugiarto; Matin (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2024)
This study explores the vital role of Kiai leadership in fostering the entrepreneurial spirit among students in Islamic boarding schools (pesantren). By integrating traditional religious values ​​with modern entrepreneurial principles, kiai leaders create a unique educational environment that encourages innovation and independence. Through qualitative research methods, including in-depth interviews and observations, this study examines how kiai leadership fosters a culture of entrepreneurship, equipping students with the skills and mindsets needed to succeed in the contemporary business world. Findings highlight the effectiveness of Kiai leadership in balancing religious teachings with practical entrepreneurial education and training, ultimately contributing to the socioeconomic development of the community.